Methdology for defining key performance indicators of development institutions as exemplified by the national project “Small and Medium-Sized Business” - A. N. Pyshkin (Вестник университета)
Approaches to the methodology for calculating key performance indicators for development institutions as part of their contribution to national development goals achievement has been reviewed. It has been shown that, depending on the methodology used, the value of this indicator can vary by up to 5 units, with each approach being relevant for a particular task. Using the example of an indicator in one of the areas of the national project “Small and Medium-Sized Business” (training activities) as an example, an integrated approach has been proposed to balance solution of the objectives of optimal spending of the federal budget and increasing the public outreach of its results.